2005
DOI: 10.1093/ajcn/82.6.1283
|View full text |Cite|
|
Sign up to set email alerts
|

Glutathione S-transferase M1 polymorphism and metabolism of sulforaphane from standard and high-glucosinolate broccoli

Abstract: GSTM1 genotypes have a significant effect on the metabolism of sulforaphane derived from standard or high-glucosinolate broccoli. It is possible that the difference in metabolism may explain the greater protection that GSTM1-positive persons gain from consuming broccoli. The potential consequences of consuming glucosinolate-enriched broccoli for GSTM1-null and -positive persons are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
2
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(259 citation statements)
references
References 23 publications
13
240
2
4
Order By: Relevance
“…This was achieved by crossing a standard cultivar with B. villosa, a wild forms of B. oleracea from Sicily, which accumulated high levels of 3-methylthiopropyl GLS in flower buds As expected, the hybrid had high levels of the target GLS, 4-methylsulphinylbutyl, due to the interaction of genes within the two parents, and a series of backcross introgressed two regions of the B. villosa genome that contained relevant QTLs for high GLS content into a commercial agronomic heading broccoli background. These high GLS broccoli cultivars have subsequently been used in human intervention trials, and shown to deliver about four times the amount of SFN to the systemic circulation than standard cultivars [64]. It is important to note that the isothiocyanates derived from these GLS contribute little to flavour, so while it is practically possible to enhance their levels, increasing levels of certain other GLSs that result in more pungent iosthiocyanates, such as 2-propenyl or 3-butenyl, may not be desirable.…”
Section: Sources Of Variationmentioning
confidence: 99%
“…This was achieved by crossing a standard cultivar with B. villosa, a wild forms of B. oleracea from Sicily, which accumulated high levels of 3-methylthiopropyl GLS in flower buds As expected, the hybrid had high levels of the target GLS, 4-methylsulphinylbutyl, due to the interaction of genes within the two parents, and a series of backcross introgressed two regions of the B. villosa genome that contained relevant QTLs for high GLS content into a commercial agronomic heading broccoli background. These high GLS broccoli cultivars have subsequently been used in human intervention trials, and shown to deliver about four times the amount of SFN to the systemic circulation than standard cultivars [64]. It is important to note that the isothiocyanates derived from these GLS contribute little to flavour, so while it is practically possible to enhance their levels, increasing levels of certain other GLSs that result in more pungent iosthiocyanates, such as 2-propenyl or 3-butenyl, may not be desirable.…”
Section: Sources Of Variationmentioning
confidence: 99%
“…One possible explanation for these findings is that the presence of GST null genotypes decreases ITC metabolism and hence increases exposure. However, studies have shown that the GSTM1 null genotype is associated with a greater rate of excretion of SFN metabolites [10] and other epidemiological studies have concluded that GSTM1 positive individuals gain greater cancer protection from cruciferous vegetable ingestion than do GSTM1 null individuals [11]. Since the effect of GST polymorphisms may be influenced by the predominant ITC consumed, there are likely to be complex interactions between ITC ingestion, genomics, and potential chemopreventive benefits.…”
Section: Chemistry and Metabolism Of Itcsmentioning
confidence: 99%
“…For example, whereas the peak plasma concentration of SFN following ingestion of 150 ml of broccoli "soup" was only ~650 nM, the total amount of SFN plus SFN metabolites (i.e. SFN-GSH, SFN-cysteineglycine, SFN-N-acetylcysteine and SFN-cysteine) was ~2 M and this rose to ~7 M following ingestion of an equivalent amount of "super-broccoli", bred to provide higher levels of ITCs [10,74]. Moreover, even partial inhibition of multiple molecular regulators that may be achieved with relatively low levels of ITCs may cooperate to provide effective suppression of angiogenesis.…”
Section: Relevance For Chemoprevention and Chemotherapymentioning
confidence: 99%
“…Results of one population-based study of ITC excretion among Chinese showed that urinary ITC was higher among GSTT1-positive, relative to GSTT1-null, individuals, but that GSTM1 and P1 genotypes had no effect [50]. In contrast, a recent pharmacokinetic study of sulforaphane disposition showed that GSTM1-null, relative to GSTM1-positive, individuals, had greater areas under the curve for plasma sulforaphane metabolite concentrations, faster rates of urinary sulforaphane metabolite excretion in the first 6 hours following consumption, and higher total excretion of sulforaphane and its metabolites over 24 h [51]. In a larger feeding study of a single meal containing 2.5 g broccoli/kg body weight, urinary ITC concentration did not differ by GSTM1, GSTP1, and GSTA1 genotypes except there was a tendency toward higher ITC excretion in GSTT1-positive individuals.…”
Section: Glutathione S-transferasesmentioning
confidence: 99%
“…Both of these studies were conducted using a single dose of broccoli, rather than more prolonged feeding that would be more comparable to habitual dietary practices among populations that routinely consume crucifers. Whether these differential responses are a function of acute versus chronic feeding or differences in the varieties of ITC present in broccoli versus crucifers commonly consumed in China remains to be established [51]; however, they speak to the further need to understand how genotype influences ITC disposition.…”
Section: Glutathione S-transferasesmentioning
confidence: 99%